Formulasi Gameksan Dalam Bentuk Mikroemulsi - Jufri, Mahdi; Binu, Asnimar; Rahmawati, Julia (UI Scholars Hub, 2004)
The clinical use of the poorly water-soluble drug substance become inefficient by means of low level penetration of such kind drug in the body. Microemulsion is a dispersion system like an emulsion which could help to increase the solubility of poorly water-soluble drug. In this research, poorly water-soluble drug is made in a dosage form of microemulsion with Gamexan as a model. An experiment has been conduct by using benzyl benzoate as an oil phase, Tween 20 with variety concentra- tion (35%;40%;45%) and sodium lauryl ether sulphate as surfactant components. The evaluation are consist of determining the amount of Gamexan in the microemulsion and stability test both physic and chemically. The result shows that all three of the microemulsion formula dosage form indicate good stability during two months of storing.